Changes in daily and cumulative volumetric rainfall at various intensity levels due to urban surface expansion over China. Issue 1 (1st January 2020) - Zhao, Deming; Zha, Jinlin; Wu, Jian
Abstract: Urban surface expansion affects land–atmosphere interactions as well as rainfall. Both the subregional area-averaged daily (DRAIN) and the subregional cumulative volumetric (VRAIN) rainfall amounts are important in this context for hydrological applications and management. Conducted at the city (Beijing, Shanghai, and Guangzhou), city cluster (Beijing–Tianjin–Hebei (BTH), the Yangtze River Delta (YRD), and the Pearl River Delta (PRD)), and national levels in China, numerical experiments were performed in this study using a regional climate model. The analysis revealed that urban-related changes in rainfall variability were more distinct for stronger rainfall among rainfalls of various intensity levels whereas changes in rainfall intensity were more pronounced for weaker rainfall. Furthermore, urban-induced changes in heavy storm rain were more prominent among rainfalls of various intensity levels, for which changes in the variability in DRAIN and VRAIN were more distinct than changes in their intensities, and exhibited marked subregional characteristics. The risk of heavy storm rain increased because of strengthened urban-induced DRAIN and VRAIN variability over Beijing, and urban areas of the YRD and China. However, the risk of heavy storm rain decreased because of decreased DRAIN and VRAIN variability and the reduced intensity of DRAIN over urban areas of Shanghai, nonurban areas of BTH, and nonurban and the entire areas of Guangzhou, the YRD, and the PRD. The urban-induced drying tendency in the lower troposphere and wetting tendency in the low–middle troposphere, and enhanced vertical motions played an important role in determining the changes in DRAIN and VRAIN in case of storm rain and heavy storm rain.